2019
DOI: 10.1136/openhrt-2019-001049
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of atrial fibrillation in patients treated with ibrutinib

Abstract: ObjectiveAtrial fibrillation (AF) is one of the most common side effects of ibrutinib, a drug that has dramatically improved the prognosis of chronic B-cell malignancies such as chronic lymphocytic leukaemia (CLL). The true incidence of ibrutinib-related AF (IRAF) is not well known and its therapeutic management poses unique challenges especially due to the inherent risk of bleeding. We aimed to determine the incidence and predictors of IRAF, and to analyse its management and outcome.MethodsA standardised moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 28 publications
0
42
0
Order By: Relevance
“…Ibrutinib, the first oral BTK inhibitor, is approved for the treatment of R/R MCL in the United States, European Union, and China on the basis of a phase II study that demonstrated overall and complete response (CR) rates of 68% and 21%, respectively (9). However, off-target inhibition of EGFR and other structurally similar kinases has been implicated in ibrutinib-associated toxicities, such as diarrhea, rash, bleeding (10,11), and atrial fibrillation (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Ibrutinib, the first oral BTK inhibitor, is approved for the treatment of R/R MCL in the United States, European Union, and China on the basis of a phase II study that demonstrated overall and complete response (CR) rates of 68% and 21%, respectively (9). However, off-target inhibition of EGFR and other structurally similar kinases has been implicated in ibrutinib-associated toxicities, such as diarrhea, rash, bleeding (10,11), and atrial fibrillation (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…• Bleeding can range from epistaxis and petechiae to major events including fatal intracerebral and gastrointestinal bleeding 15 …”
Section: Chronic Lymphocytic Leukaemiamentioning
confidence: 99%
“…• Ibrutinib may need holding if diarrhoea is ≥ grade 3 (7 stools a day over baseline) 18 Table 2. Adverse effects of the Bruton tyrosine kinase (BTK) inhibitor ibrutinib and how to manage them [15][16][17][18] therapy and so comprehensive geriatric assessments are increasingly utilised to risk stratify and guide treatment intensity in older patients or in those with complex co-morbidities. 12 Despite novel therapies, a minority of patients are still treated with a significantly immunosuppressive fludarabine-based regimen.…”
Section: Diarrhoeamentioning
confidence: 99%
“…Ibrutinib is an irreversible Bruton tyrosine kinase inhibitor used in the treatment of various B‐cell malignancies, including chronic lymphocytic leukemia (CLL)/small lymphocytic lymphoma (SLL), relapsed or refractory Mantle cell lymphoma, relapsed or refractory marginal zone lymphoma, Waldenstrom macroglobulinemia, chronic graft‐versus‐host disease, and additional off‐label uses 1,2 . Ibrutinib has been associated with the development of atrial fibrillation (AF) in approximately 6%–16% of patients, 1 though a recent prospective multicenter cohort study suggests the incidence of ibrutinib‐related atrial fibrillation (IRAF) may be as high as 38% at 2‐year follow‐up 3 . A systematic review and meta‐analysis of four randomized control trials noted the pooled relative risk of AF in ibrutinib recipients was 3.5 (95% confidence interval 1.8–6.9, P < .0001) 4 .…”
Section: Introductionmentioning
confidence: 99%
“…prospective multicenter cohort study suggests the incidence of ibrutinib-related atrial fibrillation (IRAF) may be as high as 38% at 2-year follow-up. 3 A systematic review and meta-analysis of four randomized control trials noted the pooled relative risk of AF in ibrutinib recipients was 3.5 (95% confidence interval 1.8-6.9, P < .0001). 4 Cardiovascular adverse events related to ibrutinib were associated with a 10%-20% fatality rate (with the exception of ibrutinib-associated hypertension), as per a retrospective international analysis of 303 ibrutinib-associated cardiovascular deaths.…”
mentioning
confidence: 99%